2015
DOI: 10.1111/dmcn.12840
|View full text |Cite
|
Sign up to set email alerts
|

The histopathology of polymicrogyria: a series of 71 brain autopsy studies

Abstract: PMG PolymicrogyriaAIM Polymicrogyria (PMG) is one of the most common forms of cortical malformation yet the mechanism of its development remains unknown. This study describes the histopathological aspects of PMG in a large series including a significant proportion of fetal cases.METHOD We have reviewed the neuropathology and medical records of 44 fetuses and 27 children and adults in whom the cortical architecture was focally or diffusely replaced by one or more festooning bands of neurons. RESULTSThe pial sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 55 publications
2
48
1
2
Order By: Relevance
“…We found other brain anomalies in association with PMG in 50% of our patients. This ratio is lower compared to a recent study by Jansen et al in which they stated that PMG is almost always associated with other brain malformations 15 . This may be attributable to the smaller cohort in our study and the difference in that the abovementioned study was a histopathologic one and our MRI study might not have been able to detect all malformations.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We found other brain anomalies in association with PMG in 50% of our patients. This ratio is lower compared to a recent study by Jansen et al in which they stated that PMG is almost always associated with other brain malformations 15 . This may be attributable to the smaller cohort in our study and the difference in that the abovementioned study was a histopathologic one and our MRI study might not have been able to detect all malformations.…”
Section: Discussioncontrasting
confidence: 75%
“…Histologically, there are multiple abnormal small gyri, shallow sulci and fusion of the first molecular layer in PMG 12,13 . Pial defects and abnormal vascular structures were also reported in PMG 14,15 . In addition, cortical infoldings formed by the malformed cortex were also described, however, the MRI properties of these cortical infoldings and undulations have not yet been studied 12 .…”
Section: Introductionmentioning
confidence: 92%
“…71 It is probably caused by prenatal damage to the glial limiting membrane. 72 Presentation varies with the location and the extent of the PMG, but most patients have developmental delay or behavioral problems in childhood and 70% develop seizures during the first 5 years of life. 71 Despite the large number of patients affected, PMG pathogenesis is poorly understood: It is very likely multifactorial; its presentation and outcome vary because of its causal heterogeneity; and not all disorders with multiple small gyri are true polymicrogyria, even though they have multiple small gyri and may therefore be given that diagnosis.…”
Section: Cobblestone Malformationsmentioning
confidence: 99%
“…Handicap referred to the impact that impairment and disability had on the person's role in society or the disadvantage experienced while trying to fulfill certain social roles. 4 From the beginning, the ICIDH system was ill-defined and lacked depth. 5 However, the emerging field of childhood disability adopted its language and principles.…”
mentioning
confidence: 99%
“…Mutations of these various genes may lead to radial glial instability via different means, loss of interaction with the basal membrane in the case of GPR56, and cytoskeletal destabilization for TUBB2B. 3 Jansen et al 4 studied the histopathological aspects of PMG in 44 fetuses and 27 children and adults in whom the cortical architecture was focally or diffusely replaced by one or more festooning bands of neurons. They showed that the pial surface of the brain overlying the polymicrogyric cortex was abnormal in almost 90% of their cases irrespective of the aetiology, suggesting an important role for the leptomeninges in cortical development.…”
mentioning
confidence: 99%